Structural and physicochemical characterisation and antioxidant activity of an α-D-glucan produced by sourdough isolate Weissella cibaria MED17 - Aburas, Hani; Ispirli, Humeyra; Taylan, Osman; Yilmaz, Mustafa Tahsin; Dertli, Enes (ELSEVIER, 2020)
An exopolysaccharide (EPS) producer slimy-mucoid type colony was isolated from sourdough and identified as Weissella ciboria MED17. The H-1 and C-13 NMR spectra of EPS MED17 demonstrated that this EPS was a dextran type glucan ((1 -> 6)-linked alpha-D-glucose core structure) containing (1 -> 3)-linked alpha-D-glucose branches and proportion of (1 -> 6)-linked alpha-D-glucose units to (1 -> 3)-linked alpha-D-glucose units was 943:5.7%. The MR analysis also confirmed the (1 -> 6)-linked alpha-D-glucose linkage. A high level of thermal stability was observed for glucan MED17 as no degradation up to 300 degrees C was observed by TGA and DSC analysis. The XRD analysis of glucan MED17 showed its semi- crystalline nature and its compact sheet-like morphology was observed by SEM analysis. Finally, antioxidant characteristics of glucan MED17 were determined by ABTS and DPPH radical scavenging activity tests that revealed a moderate antioxidant activity of glucan MED17. These findings show potential techno-functional characteristics of glucan MED17. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Exopolysaccharides; Antioxidant polysaccharides; Functional roles; GLUTEN-FREE; LACTOBACILLUS; DEXTRAN; GLUCANSUCRASE; BIOACTIVITY; ENZYMES; WHEAT; Biochemistry & Molecular Biology; Chemistry; Polymer Science